Pengaruh Green Accounting, Kinerja Lingkungan, dan Struktur Modal Terhadap Kinerja Keuangan - Siti Rokhmah; Nafi’ Inayati Zahro; Retno Tri Handayani (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2026)
Financial performance is an important indicator used to assess a company’s ability to generate profits and maintain business sustainability. Along with the increasing demand for environmental responsibility and efficient financing decisions, companies are required to improve financial performance through sustainable business practices. This study aims to examine the effect of green accounting, environmental performance, and capital structure on the financial performance of consumer non-cyclical companies listed on the Indonesia Stock Exchange during 2020–2024. This study employed a quantitative approach using secondary data obtained from annual reports and sustainability disclosures. The sampling technique used purposive sampling and resulted in 22 companies with 110 observations. Data analysis was conducted using panel data regression with the Fixed Effect Model (FEM). The results indicate that green accounting does not affect financial performance. Environmental performance also has no effect on financial performance. Meanwhile, capital structure has a negative effect on financial performance. The model demonstrates strong explanatory power with an Adjusted R-Squared value of 81.6%. These findings indicate that environmental disclosure practices and environmental achievements have not yet become the primary determinants of financial performance in consumer non-cyclical companies. On the other hand, financing policies reflected through capital structure play a more significant role in influencing corporate profitability. This study contributes to the development of stakeholder theory and signaling theory in explaining financial performance in environmentally oriented companies.